Campanhas da fraternidade e educação: qual educação e para qual cristão? - Moreira, Mateus Martins (2023)
The present research was developed in the Area of Society, Knowledge and Education, of the Postgraduate Program of the Universidade Estadual do Oeste do Paraná – Unioeste – Campus of Francisco Beltrão. In it, we developed a documentary analysis that had as its main source the Base Texts of the Fraternity Campaigns (FC) of the years 1982, 1998 and 2022, in their respective historical contexts. We carried out this investigation with the aim of understanding the formative project for Christians proposed in these three editions of the FC, which central theme was Education. The theme of education was approached from an interdisciplinary perspective, seeking to understand the historical, philosophical, theological and educational foundations that served as the theoretical foundation for the three FCs. The central question was to understand which project and/or conception of education was/is present in the texts of the Fraternity Campaign? To answer it, we used the method of historical-dialectical materialism, which, starting from the appearance of things, aims to reach their essence, generating theoretical knowledge about the structures and their dialectical movement, reproducing in the plane of thought, the essence of the object we are investigating. Our analysis was based on a counterhegemonic critical pedagogical perspective in dialogue with the philosophy and Theology of Latin American Liberation. We chose to make a critical assessment of the concepts; liberating education, evangelizing education and integral education that appeared in the Base Texts (BT) of FC. Our analysis took place within the forty-year historical period between the first and third FC. In this space of time we identified three perspectives that either subsidized or influenced the analysis: in 1982 a clearly progressive perspective; in 1998 an occultly conservative outlook; in 2022 a subtly moderated analysis. In this process, we identified a progressiveconservative dialectic within the ecclesial universe, generating ruptures and continuities that influenced/influenced the educational reflection present in the three Basic Texts and in the very action of Christians and the Church in society.